Improving students' value perception and decision-making skills through socioscientific issue-based physics teaching - Masauring, Lyneth Deisserrie B. (College of Education, University of the Philippines Diliman, 2019)
This study investigated the effect of Socioscientific Issue-Based Physics Teaching (SSPT) on students value perception and decision-making skills. In addition, the study probed the effect of students value perception in decision-making. It also investigated the extent to which youth culture moderated the effects of SSPT on students value perception and decision-making. The study utilized the quasi-experimental two-group pretest-posttest quasi-experimental design. Sixty eight Grade 10 high school students from a private sectarian school in Isabela participated in the study, Two intact classes were randomly assigned as SSPT and Conventional Physics Teaching (CPT) group. Both classes were taught by the researcher. The study was done during the first quarter (June to August) of the academic year 2015-2016. The The researcher-made instruments in the study were Value Perception in Science Inventory (VPSI), Physics Decision-Making Skills Test (PDST), and Youth Culture Questionnaire (YCQ). These instruments were validated by a panel of experts and were pilot-tested, and administered in pretest and posttest. Factor analysis was conducted to determine the components of value perception in science and youth culture, t-test for independent samples was used to compare the mean pretest and posttest scores of VPSI and PDST. This was done to establish the comparability of SSPT and CPT before the intervention and to determine if there was a significant difference between SSPT and CPT after the intervention. Linear regression was employed to investigate if students value perception positively predicted decision-making skills. Lastly, two-way analysis of Variance (ANOVA) was performed to determine whether youth culture moderate the effects of SSPT on students value perception and decision-making skills. One-way ANOVA was also utilized to determine the simple main effects of SSPT on each youth culture. Results revealed that SSPT is more effective in improving students value perception and decision-making skills than CPT. Also, students value perception predicted decision-making skills. Lastly, youth culture moderated the effects of SSPT on students value perception and decision-making skills. Further investigation can be undertaken on the effects of SSPT on the other twenty six first century skills such as critical thinking and problem solving. Moreover, it is also recommended that instruments used in this study be used by the stakeholders in the field of education. Also, there are very limited studies conducted on students value perception; that it is recommended to explore more on the construct and investigate how it affects students affective and cognitive domain. Finally, it is recommended to further analyzed youth culture and its effect on students learning process.